Acute kidney injury in COVID‐19: Identification of risk factors and potential biomarkers of disease in a large UK cohort. Issue 5 (7th January 2021) - Phillips, Thomas; Stammers, Matthew; Leggatt, Gary; Bonfield, Becky; Fraser, Simon; Armstrong, Kirsten; Veighey, Kristin
Abstract: Background: COVID‐19 is associated with increased risk of acute kidney injury (AKI). Risk factors and biomarkers linked to AKI have now been recognized by national guidelines in the United Kingdom. This analysis aims to validate and expand the comorbidities and biomarkers associated with the presence and severity of AKI in these patients. Methods: Data were extracted via structured query language for patients with COVID‐19 at University Hospital Southampton between 1 March and 10 June 2020. Demographics, comorbidities, common biomarkers and AKI stage within 48 hours of admission, peak during admission and the last measurement prior to patient outcome (discharge or death) were collected and statistically analysed. Results: Six hundred and thirty‐two COVID‐19 positive patients were admitted during this period; 34.2% had an AKI during their entire admission, 20.3% had AKI stage 1, 8.5% stage 2 and 5.4% stage 3. This was higher when compared with data from the same period in 2019. AKI carried an increased risk of death, 50.0% vs 21.1% ( P = <.001). AKI stage was significantly associated with age over 65, diabetes, heart failure, peripheral vascular disease, haematological malignancy, hypertension, respiratory rate, albumin, C‐reactive protein (CRP), d ‐dimer, ferritin, high‐sensitivity troponin‐I, neutrophil count, total white cell counts, National Early Warning Score‐2 (NEWS‐2), Charlson comorbidity index and alanine‐aminotransferase. COVID‐19 specific treatment, including dexamethasone, reduced discharge creatinine. Conclusion: COVID‐19 increases the risk of AKI and this kidney injury may be responsive to treatment. This analysis identified that AKI is associated with both previously described and new comorbidities and biomarkers. SUMMARY AT A GLANCE: This study reviewed biomarkers and comorbidities linked to AKI associated with COVID‐19 infections in 632 patients. 34.2% developed AKI with a 50% increased mortality. Severity of AKI was linked to both comorbidities and biomarkers.